2015
DOI: 10.1210/me.2014-1304
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of the lncRNA MEG3 and Its Target c-MET in Pancreatic Neuroendocrine Tumors

Abstract: Biallelic inactivation of MEN1 encoding menin in pancreatic neuroendocrine tumors (PNETs) associated with the multiple endocrine neoplasia type 1 (MEN1) syndrome is well established, but how menin loss/inactivation initiates tumorigenesis is not well understood. We show that menin activates the long noncoding RNA maternally expressed gene 3 (Meg3) by histone-H3 lysine-4 trimethylation and CpG hypomethylation at the Meg3 promoter CRE site, to allow binding of the transcription factor cAMP response element-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
104
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 46 publications
5
104
0
2
Order By: Relevance
“…c-MET amplification and mutations have not been observed in the exome sequencing efforts of PNETs and insulinomas (5-7). However, increased c-MET level in human PNETs and insulinomas has been observed (16,17). We previously showed in mouse insulinoma MIN6 ␤-cells that c-Met mRNA could be down-regulated by a menin target, the long non-coding RNA Meg3, and a commonly used c-Met inhibitor (PHA-665752) suppressed the growth and migration of mouse insulinoma MIN6 ␤-cells (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…c-MET amplification and mutations have not been observed in the exome sequencing efforts of PNETs and insulinomas (5-7). However, increased c-MET level in human PNETs and insulinomas has been observed (16,17). We previously showed in mouse insulinoma MIN6 ␤-cells that c-Met mRNA could be down-regulated by a menin target, the long non-coding RNA Meg3, and a commonly used c-Met inhibitor (PHA-665752) suppressed the growth and migration of mouse insulinoma MIN6 ␤-cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-fixed paraffinembedded pancreas tissue sections from pancreatic islet tumor-bearing18-month-old Men1 ϩ/Ϫ mice (32), 12-monthold Men1 f/f (with germ-line homozygous floxed Men1), and 12-month-old pancreatic islet tumor-bearing RIP-Cre-Men1 f/f mice (␤-cell-specific Men1 knock-out; germ-line homozygous floxed Men1 with conditional expression of Cre-recombinase in ␤-cells from the Rat insulin promoter) (33) were stained for insulin using standard IF procedures. For IHC, formalin-fixed paraffin-embedded pancreas sections were processed as previously described (10,17) for HB9, HB9-PO4, Cblb, and c-Met staining. After IF and IHC, images were captured on the BZ9000 microscope (Keyence).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that lncRNA MEG3, a tumor suppressor gene, was down-regulated in various cancers and was associated with poor prognosis (14)(15)(16)(17)(18). A previous study indicated that the expression of lncRN A MEG3 was clearly lower in osteosarcoma tissues compared with adjacent non-tumor tissues (19).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al suggested that MEG3 functions as a tumor suppressor in hepatoma cells through interacting with p53 protein (18). In addition to these studies, the role of MEG3 has been investigated in gallbladder cancer, NSCLC, neuroendocrine tumor, gastric cancer, thyroid carcinoma and so on (25,(14)(15)(16)(17). However, to the best of our knowledge, the potential roles of MEG3 in OS remain largely unknown.…”
mentioning
confidence: 99%